Pengaruh Kualitas Pelayanan, Kualitas Produk dan Harga terhadap Loyalitas Pelanggan dengan Kepuasaan Pelanggan Sebagai Variabel Mediasi: (Studi Kasus Rumah Makan di Waduk Malahayu Brebes) - Deri Prayoga; Haerudi Haerudi; Edy Purwanto (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Customer loyalty is an important factor in maintaining the sustainability of restaurant businesses amid increasingly intense competition in the culinary industry. This study aims to analyze the influence of service quality, product quality, and price on customer loyalty with customer satisfaction as a mediating variable at Waduk Malahayu Restaurant, Brebes. This research used a quantitative approach with a survey method through the distribution of questionnaires to 100 respondents who were customers of Waduk Malahayu Restaurant. The sampling technique used was accidental sampling. Data analysis was conducted using the Partial Least Square (PLS) method with the assistance of SmartPLS version 3 software. The results of the study indicate that service quality has no effect on customer loyalty, product quality has no effect on customer loyalty, and price has a positive and significant effect on customer satisfaction. Customer satisfaction is unable to mediate the relationship between service quality and customer loyalty, while customer satisfaction is able to mediate the relationship between product quality and customer loyalty, as well as the relationship between price and customer loyalty. In addition, customer satisfaction has a positive and significant effect on customer loyalty. These findings indicate that product quality, price suitability, and customer satisfaction are the main factors in increasing customer loyalty at Waduk Malahayu Restaurant, Brebes. Therefore, the restaurant management needs to maintain product quality, improve service, and set appropriate prices in order to retain customer loyalty and encourage repeat purchases in the future.